Socioeconomic status and body mass index life course models: the 1993 Pelotas (Brazil) birth cohort - Luna Strieder Vieira; Juliana dos Santos Vaz; Fernando César Wehrmeister; Felipe Garcia Ribeiro; Janaína Vieira dos Santos Motta; Helen Denise Gonçalves da Silva; Maria Cecília Formoso Assunção (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: This article aims to assess the relationship between an individual's socioeconomic status over their life-course and their body mass index (BMI) at 22 years of age, according to the hypotheses generated by risk accumulation, critical period, and social mobility models. This was a population-based prospective study based on the Pelotas (Brazil) 1993 birth cohort. The risk accumulation, critical period, and social mobility models were tested in relation to a saturated model and compared with a partial F-test. After the best model was chosen, linear regression was carried out to determine the crude and adjusted regression coefficients of the association between socioeconomic status over the life-course and BMI at 22 years of age. The sample was comprised of 3,292 individuals (53.3% women). We found dose-response effect for both men and women, although the results were opposite. Among men, a lower score in socioeconomic status accumulation model led to a lower BMI average at 22 years of age; whereas among women, a lower score in socioeconomic status accumulation model caused an increase in BMI at 22 years of age.